Genotypic and Phenotypic Variability of Seedling Tolerance to Salinity of Rice Germplasm - Edem, A.W. (University Of Ghana, 2015)
Soil salinity is one of the most important factors retarding rice growth and development at both vegetative and reproductive stages. This is becoming a major challenge in the production of rice in Ghana and Africa as a whole. This has necessitated the breeding of salt tolerant lines for the future, since population and hence consumption of rice is always on the increase. Thirty-two (32) rice accessions including four (4) checks were screened for salinity tolerance and also used in diversity studies, in order to select accessions for breeding programs. Pregerminated seeds were sown in Styrofoam hydroponic system. Salinity stress was induced after the third day by replacing the distilled water with nutrient solution with an initial EC of 6 dS/ m. The salinity was increased by adding NaCl to attain an EC of 12 dS/ m by the third day whiles maintaining the pH of the solution at 5.0 daily. Visual scoring for stress symptoms was done after 12 days with the aid of the checks to separate the accessions. Shoot samples of each entry were collected and washed carefully with distilled water. They were Oven-dried for 3 days at 70 oC. The dried samples were ground to obtain about 1 g (40 mesh) powder per accession and the Na and K ion concentrations were determined using flame photometer. Genetic diversity studies was carried with 33 SSR primers, 20 of which were markers for salt tolerance. 28 out of the 33 primers were polymorphic. The PCR products were run and visualized on a 3% agarose gel matrix stained with ethidium bromide. Amplified bands were scored and analyzed with PowerMarker v3.25 and DARwin v5 software .The genetic diversity among the accessions assembled was high (He=0.6, I=0.516Primers RM10711 and RM10793 were the only primers able to completely discriminate tolerant genotypes from susceptible ones, hence can be used in selections involving the genotypes. Accessions SR1, IR72, Sebota 337-1, Perfume (Short) type, Anyofula, Local Red, GR18Red, GH1580, GH1528, GH1575, NericaL23, NericaL24 and NericaL27 performed well under salinity stress in this study and were identified to be superior among the accessions used, PIC=0.471). Saltol
MPhil.
Keywords: Genotypic; Phenotypic; Seedling; Soil Salinity; Rice Germplasm; Genetic Diversity; Ghana